Profiling Climate Smart Agriculture for Southern Coastal Region of Bangladesh and its Impact on Productivity, Adaptation and Mitigation - Ali, M Yusuf; Hossain, Mohammed Emdad (2019)
Now a days ensuring sustainable food security is a great concern because of devastating effects of climate change on the most vulnerable country like Bangladesh. Its coastal southern region agriculture and peoples livelihood is mostly affected by recurrent cyclone, tidal surge, flood, salinity and dearth of appropriate technology options to manage those. Applying climate smart agricultural practices at community level could minimize the climate change related effects. Thus, climate smart agriculture (CSA) practices those are used and developed by local community, innovator, extension workers and agricultural researchers are being collected through desktop work, survey, field visit, personal communication and focus group discussion. Lastly through expert level workshop 41 CSA practices were selected under 13 major production systems. Through written questionnaire expert evaluated the production practices and gave climate smartness score for each practice along with their impact on three pillars of CSA viz. productivity, adaptation and mitigation. The major production systems were selected as per their contribution to food production and livelihoods. Those production systems are T.aman rice, boro rice, aus rice, jute, spices, oilseeds, vegetable, wheat, pulses, maize, fruit, pond and floodplain aquaculture, and livestock. Climate smartness score largely varied (0.60 to 3.93) because of positive, negative and neutral effect on different criteria. However, most of the production practices have positive effect on production, adaptation and carbon sequestration. Some have impact on reducing greenhouse gas (GHG). Therefore, adoption/adaptation of these production practices would be instrumental to mitigate/minimize the detrimental effect of climate change towards achieving food security and to conduct further research and development work.